Diabetic retinopathy, tactics for patients - Abdurakhmonov Niyozbek Khamdamjon ogli (Peerian Journals Publishing, 2023)
An analysis of the prevalence of ophthalmic complications in patients with Type 1 and 2 diabetes mellitus, as well as the main causes of disability with this pathology is presented. The main methods of treatment of prediabetic and proliferative retinopathy are covered. The use of the presented tactics reduces the incidence of blindness and helps to improve the quality of life of patients with diabetes.
Keywords: Diabetic retinopathy; panretinal laser coagulation; intravitreal Drug Administration